1998
DOI: 10.5511/plantbiotechnology.15.205
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Novel Glutelin cDNA from Rice Seeds.

Abstract: A novel glutelin gene was cloned from a cDNA library of maturing rice seeds (Oryza sativa L. cv Nipponbare) . The 2.0kbp insert contained an open reading frame encoding a 510 amino acid polypeptide (Mr 57,116). This novel glutelin shares 46 to 49% amino acid identity with previously identified rice glutelins. A phylogenetic analysis of cloned glutelins indicates that this gene constitutes a new, fifth class of glutelin gene families. The Asn-Gly processing sequence which is highly conserved in 11S seed storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…A recent transcriptional profiling study of six members from the GluA and GluB subfamilies showed that none of them had any detectable expression level at three DAF but with a peak activity at 10 DAF before declining toward maturation (20 DAF) (Duan and Sun 2005). This common pattern was also discovered in other studies on GluA, GluB, and GluC subfamily members (Okita et al 1989;Takaiwa andOono 1990, 1991;Mitsukawa et al 1998). GluD-1, however, is different from the other glutelin genes.…”
Section: Protein Composition Of Rice Grain Is Mainly Determined By Glsupporting
confidence: 62%
See 2 more Smart Citations
“…A recent transcriptional profiling study of six members from the GluA and GluB subfamilies showed that none of them had any detectable expression level at three DAF but with a peak activity at 10 DAF before declining toward maturation (20 DAF) (Duan and Sun 2005). This common pattern was also discovered in other studies on GluA, GluB, and GluC subfamily members (Okita et al 1989;Takaiwa andOono 1990, 1991;Mitsukawa et al 1998). GluD-1, however, is different from the other glutelin genes.…”
Section: Protein Composition Of Rice Grain Is Mainly Determined By Glsupporting
confidence: 62%
“…; Takaiwa and Oono , ; Mitsukawa et al. ). GluD‐1 , however, is different from the other glutelin genes.…”
Section: Molecular Basis Of Grain Quality In Ricementioning
confidence: 99%
See 1 more Smart Citation
“…, 1982) (Figure 2). Processing sites (Asn‐Gly) are highly conserved, but there are some deviations, such as Asn‐Val in GluC (Mitsukawa et al. , 1998).…”
Section: Processing and Transport Of Sspmentioning
confidence: 99%
“…After trafficking to the PB-II as trimers by two routes, proglutelins are processed by vacuolar protein enzyme (VPE), generating both the mature acidic and the basic subunits that are linked by a disulphide bond Yamagata et al, 1982) (Figure 2). Processing sites (Asn-Gly) are highly conserved, but there are some deviations, such as Asn-Val in GluC (Mitsukawa et al, 1998). When GluA-2 was mutated to a noncleavable form, deposition was not affected, but higher-order structure formation was perturbed .…”
Section: Processing and Transport Of Sspmentioning
confidence: 99%